Carcinoma pigmentado de células escamosas de la piel - Quirós, José Luis (2009)
A case of a male patient of 88 years, who presents a skin dark color lesion in the left malar region. Through a biopsy determined that consisted of a pigmented squamous cell carcinoma. This type of tumor is unusual. 7% of cases of squamous cell cancer of only 0.01% had pigment, which leads to make differential diagnosis with melanoma, a malignant skin tumor with very poor prognosis.The attraction of the event is the description of a squamous cell carcinoma that presents an accompanying population of cells positive for immunohistochemical markers of HMB-45 and S-100, typical markers of melanoma, a very infrequently case.